2014
DOI: 10.5433/1679-0359.2014v35n5p2723
|View full text |Cite
|
Sign up to set email alerts
|

Glycerin and cashew and castor oils in the diets for bulls in finished in feed lot: ingestive behavior

Abstract: This study was carried out to evaluate partial replacing of corn (15% of total diet DM) and cashew and castor oils addition on ingestive behavior of Nellore bulls in feedlot. Thirty bulls of 24 ± 2 months old and 400 ± 34 kg body weight were used. The bulls were distributed in a completely randomized design (10 bulls per treatment) and housed in collective pens. The experimental diets were: Control -CON; Glycerine -GLY and Glycerine + Functional oils. The observation scales did not influence time spent eating,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
6
0
1
Order By: Relevance
“…Despite the lack of significant difference in propionic acid concentrations, the combination crude glycerine with essential oil promoted an increase of 17% in this acid, fact that decreased the C2: C3 ratio in the rumen. Although there are also evidence that crude glycerine may have a detrimental effect on the growth of structural carbohydrate fermenting bacteria (AbuGhazaleh, Abo El‐Nor, & Ibrahim, ; Roger, Fonty, Andre, & Gouet, ), resulting in reduced fibre digestibility and CH 4 production (van Cleef et al, ; Homem Junior et al, ; Paschoaloto et al, ), crude glycerine does not impair the consumption, performance or carcass characteristics of feedlot cattle (van Cleef et al, ) and, when combined with essential oil, has shown even better results (Cruz et al, ; Prado et al, ; Silva et al, ; Valero, Prado, et al, ; Valero, Torrecilhas, et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the lack of significant difference in propionic acid concentrations, the combination crude glycerine with essential oil promoted an increase of 17% in this acid, fact that decreased the C2: C3 ratio in the rumen. Although there are also evidence that crude glycerine may have a detrimental effect on the growth of structural carbohydrate fermenting bacteria (AbuGhazaleh, Abo El‐Nor, & Ibrahim, ; Roger, Fonty, Andre, & Gouet, ), resulting in reduced fibre digestibility and CH 4 production (van Cleef et al, ; Homem Junior et al, ; Paschoaloto et al, ), crude glycerine does not impair the consumption, performance or carcass characteristics of feedlot cattle (van Cleef et al, ) and, when combined with essential oil, has shown even better results (Cruz et al, ; Prado et al, ; Silva et al, ; Valero, Prado, et al, ; Valero, Torrecilhas, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of significant difference in propionic acid concentrations, the combination crude glycerine with essential oil promoted an increase of 17% in this acid, fact that decreased the C2: C3 ratio in the rumen. (Cruz et al, 2014;Prado et al, 2016;Silva et al, 2014;Valero, Torrecilhas, et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grande parte das pesquisas está relacionada ao ambiente ruminal e atualmente diversos estudos vêm sendo realizados no Brasil, principalmente com relação à utilização desses óleos em substituição à ionóforos , Silva et al, 2014, Valero et al, 2014a, Valero et al, 2014b, Zawadzki et al, 2015, Cruz et al, 2014 Na alimentação animal é importante conhecer profundamente qual produto está sendo empregado, além de seu princípio ativo, controle de qualidade e estabilidade. Sabe-se que o cardol e o ácido ricinoléico agem na parede das bactérias gram-positivas como ionóforos naturais e que misturas destes produtos tem atividade anticoccidiana (Oliveira et al, 2011), controlam o pH ruminal e melhoram a digestibilidade da fibra e possuem efeitos na características da carcaça (Torrent, 2014).…”
Section: óLeos Essenciais Na Nutrição De Ruminantesunclassified
“…Functional oils are defined as oils that have an action beyond their nutritional value (Murakami et al, 2014) and are not derived from essences or spices (Bess et al, 2012), but from oil plants such as castor seeds (Ricinus communis) and cashew nutshell (Anacardium occidentale; Silva et al, 2014).…”
Section: Introductionmentioning
confidence: 99%